Factors Affecting Conception Rate in AI Bred Cattle under Field Conditions of Maharashtra - Potdar, Vinod V.; Khadse, Jayant R; Joshi, Sachin; Swaminathan , Marimuthu (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Data on 98336 artificial inseminations (AI) performed during 6 years (January 2010 to November 2015) on 56037 field animals owned by 29097 farmers’ from 44 cattle development centres spread across two districts of Maharashtra state were collected and analyzed. Whole data set was classified according to districts (Beed, Jalgaon), economic status of farmers (APL, BPL), animal breed (HF cross, Indigenous, Jersey cross, Non-descript), parity of animal (heifer, first, second, third, fourth, fifth calvers), animal body condition score (no rib exposed, one rib exposed, two ribs exposed, three ribs exposed), heat stage (early, mid, late), season of AI (rainy-June to September, winter-October to January, summer-February to May), bull breed used for AI ( HF, HF crossbreed, Jersey, Jersey crossbreed, Indigenous), AI sequence number (1,2,3) and AI Year (2010 to 2015). Least square analysis was used to compute conception rate. The results revealed overall mean conception rate as 46.2 ± 0.51% and it was significantly (p<0.01) higher in Beed district, Jersey crossbreed animals, animals having fourth parity, animals exhibiting one rib exposed, early heat and animals inseminated with Indigenous breed bulls semen, first AI sequence number and during the year 2015 compared with respective groups of parameters under study. However, effect of season of AI and economic condition of farmers did not affect conception rate in animals under field conditions of Maharashtra.